2009
DOI: 10.1158/1055-9965.epi-08-0741
|View full text |Cite
|
Sign up to set email alerts
|

Lung Adenocarcinoma Incidence Rates and Their Relation to Motor Vehicle Density

Abstract: Background and Objective: The temporal trend of adenocarcinoma incidence rates of the lung (ADL) has been reported to parallel the trend of nitrogen oxide (NO x ) emissions in the United States. This study explores the geographic pattern of ADL incidence and its relation to motor vehicle density, the major indicator of NO x emissions before 1970. Methods: ADL incidence rates by counties were retrieved from the nine sites of Surveillance, Epidemiology, and End Results (SEER) Program for the period of 1973 to 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 13 publications
0
32
1
2
Order By: Relevance
“…The incidence rates of squamous cell and small-cell carcinomas of the lung increased during the 1970s, peaked at the beginning of the 1980s, and decreased thereafter, whereas the incidence rate of adenocarcinoma of the lung first decreased from about 1998. An association between NO x air pollution and adenocarcinoma of the lung has been suggested as the explanation for these different time trends, supported by ecological correlations between the incidence rates of adenocarcinomas and vehicle densities at county area level (29,30). Use of individual exposure assessments in our study did not confirm this hypothesis because we observed stronger associations between NO x concentrations and risk for squamous cell and small-cell carcinomas than for adenocarcinoma of the lung.…”
Section: Discussioncontrasting
confidence: 58%
“…The incidence rates of squamous cell and small-cell carcinomas of the lung increased during the 1970s, peaked at the beginning of the 1980s, and decreased thereafter, whereas the incidence rate of adenocarcinoma of the lung first decreased from about 1998. An association between NO x air pollution and adenocarcinoma of the lung has been suggested as the explanation for these different time trends, supported by ecological correlations between the incidence rates of adenocarcinomas and vehicle densities at county area level (29,30). Use of individual exposure assessments in our study did not confirm this hypothesis because we observed stronger associations between NO x concentrations and risk for squamous cell and small-cell carcinomas than for adenocarcinoma of the lung.…”
Section: Discussioncontrasting
confidence: 58%
“…Likewise, average NO 2 concentrations reported by the EPA have increased 169% from 1960 to 1979, followed by a decline of 44% in the monitoring concentration of NOx from 1980 to 2007. (4,5) The peak year of the incidence curve was 20 years later than the peak of the curve of NOx pollutants.…”
Section: Resultsmentioning
confidence: 99%
“…Later research proposed the possibility that lung adenocarcinoma is a disease whose long-term incidence trend is associated with variation of nitrogen oxides (NOx), a family including Nitric oxide (NO) and nitrogen dioxide (NO 2 ), and several other nitrogen-oxygen compounds of air pollution, and the geographic distribution pattern of lung adenocarcinoma is highly related to motor vehicle density, a major source of NOx (R 2 0.8052). [3,4] Given that breast cancers are also diagnosed as adenocarcinoma and its incidence rises along with industrialization, further study is needed to explore possible linkages between the upward-downward trend of breast cancer incidence and air quality. In addition to comparing the long-term trend, an analysis of the geographical pattern is needed to see whether there is a doseresponse relationship between incidence and the level of air pollution in different areas.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, residences near industrial areas are significantly associated with various disease incidences including lung cancer (37)(38)(39); green spaces have a positive impact on health, including decreasing respiratory disease mortality (40)(41)(42), while the impact may not always significant in certain areas (43). Meanwhile, since high traffic volume increases incidence rate of pulmonary adenoma (44,45), living within 100 m from highways has a negative impact on respiratory health for both children (46,47) and adults (48). Current studies have respectively explored the indoor and outdoor factors on respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%